Self-regulation and Learning Strategies of Beginner and Advanced University Students - Cecilia Belletti; Denise Vaillant (Universidad ORT Uruguay, 2022)
The authors analyze the self-regulation learning processes of university students from a degree in the area of computer systems in a private University in Uruguay. An analysis is made of the main features that characterize self-regulation processes drawn from a quant-qual investigation based on a pre-existing questionnaire adapted to this particular context. Such is the Motivated Strategies for Learning Questionnaire (MSLQ), which was administered to 187 students; semi-structured interviews were also carried out to 10 students. Among the most important results of the study, it is worth emphasizing the high level of intrinsic and extrinsic motivation and the diversity in the self-regulation learning strategies used by beginner and advanced students. Concerning the cognitive strategies, students mainly use deep information-processing strategies. Some of the self-regulation processes are developed in keeping with the beginner and advanced students' academic progress.